Factores protectores y de riesgo relacionados con las enfermedades diarreicas agudas en niños de 1 a 3 años de la Zona 7 del Ecuador. - Sánchez Díaz, Nancy Marleny (2017)
Acute diarrheal diseases are a public health problem in most of developing countries, constituting the second morbidity and mortality in five years old children; being presented in all ages but frequently in children under five years old. Due that, a descriptive, prospective, analytic and transversal study was carried out in the Well Living Infant Centers of the Zone 7. This, with the objective of characterize socio-demographic conditions, identify the protection and risk factors and its association with the acute diarrheic disease in 1 to 3 years old aged children. For that, a randomly sample was used from 423 children. A structured survey directed to the parents of the families or representatives of children was used, that determined the different aspects concerning to acute diarrheas. It was determined the familiar function range through the evaluation test of intra familiar relationships (FFSIL) and the survey of the Statistic and Census Ecuadorian Institute (INEC), for life conditions of the participants. Among the relevant results, there is a general prevalence of acute diarrhea (24.8), with higher proportion in masculine gender (55,2%), of one year old (46,67%), residents of El Oro province (42,86%) in the urban sector (70,48%). About family characteristics, there was higher prevalence of acute diarrheal diseases in median families (56,19%), monoparenteral family (34,29%) and functional family (49,52%). Concluding, that there was not determined statistical significance between familiar, socioeconomic and demographic characteristics with acute diarrheal disease. Keywords: diarrheic disease, breastfed, family, socio demographic factors.